A new classification of spin in systematic reviews and meta-analyses was developed and ranked according to the severity - Yavchitz, A; Ravaud, P; Altman, DG; Moher, D; Hrobjartsson, A; Lasserson, T; Boutron, I (Elsevier, 2016)
Objectives We aimed to (1) identify and classify spin (i.e., a description that overstates efficacy and/or understates harm) in systematic reviews and (2) rank spin in abstracts of systematic reviews according to their severity (i.e., the likelihood of distorting readers' interpretation of the results).